U.S.-China Pharmacology Symposium: Proceedings (The National Academies Press, 1980)

Recapturing NASA's Aeronautics Flight Research Capabilities - National Research Council (The National Academies Press, 2012)
In the five decades since NASA was created, the agency has sustained its legacy from the National Advisory Committee on Aeronautics (NACA) in playing a major role in U.S. aeronautics research and has contributed substantially to United States preeminence in civil and military aviation. This preeminence has contributed significantly to the overall economy and balance of trade of the United States through the sales of aircraft throughout the world. NASA's contributions have included advanced flight control systems, de-icing devices, thrust-vectoring systems, wing fuselage drag reduction configurations, aircraft noise reduction, advanced transonic airfoil and winglet designs, and flight systems. Each of these contributions was successfully demonstrated through NASA flight research programs. Equally important, the aircraft industry would not have adopted these and similar advances without NASA flight demonstration on full-scale aircraft flying in an environment identical to that which the aircraft are to operate-in other words, flight research. Flight research is a tool, not a conclusion. It often informs simulation and modeling and wind tunnel testing. Aeronautics research does not follow a linear path from simulation to wind tunnels to flying an aircraft. The loss of flight research capabilities at NASA has therefore hindered the agency's ability to make progress throughout its aeronautics program by removing a primary tool for research. Recapturing NASA's Aeronautics Flight Research Capabilities discusses the motivation for NASA to pursue flight research, addressing the aspects of the committee's task such as identifying the challenges where research program success can be achieved most effectively through flight research. The report contains three case studies chosen to illustrate the state of NASA ARMD. These include the ERA program and the Fundamental Research Program's hypersonics and supersonics projects. Following these case studies, the report describes issues with the NASA ARMD organization and management and offers solutions. In addition, the chapter discusses current impediments to progress, including demonstrating relevancy to stakeholders, leadership, and the lack of focus relative to available resources. Recapturing NASA's Aeronautics Flight Research Capabilities concludes that the type and sophistication of flight research currently being conducted by NASA today is relatively low and that the agency's overall progress in aeronautics is severely constrained by its inability to actually advance its research projects to the flight research stage, a step that is vital to bridging the confidence gap. NASA has spent much effort protecting existing research projects conducted at low levels, but it has not been able to pursue most of these projects to the point where they actually produce anything useful. Without the ability to actually take flight, NASA's aeronautics research cannot progress, cannot make new discoveries, and cannot contribute to U.S. aerospace preeminence.

Advanced Technology for Human Support in Space - National Research Council (The National Academies Press, 1997)
Advanced Technology for Human Support in Space was written in response to a request from NASA's Office of Life and Microgravity Sciences and Applications (OLMSA) to evaluate its Advanced Human Support Technology Program. This report reviews the four major areas of the program: advanced life support (ALS), environmental monitoring and control (EMC), extravehicular activities (EVA), and space human factors (SHF). The focus of this program is on long-term technology development applicable to future human long-duration space missions, such as for a hypothetical new mission to the Moon or Mars.

Recent Trends in U.S. Aeronautics Research and Technology (The National Academies Press, 1999)

Readiness for the Upcoming Solar Maximum (The National Academies Press, 1998)
Get your sunglasses on and get ready for the upcoming Solar Maximum.

U.S.-European-Japanese Workshop on Space Cooperation: Summary Report (The National Academies Press, 1999)

Toxicological Risks of Selected Flame-Retardant Chemicals - National Research Council (The National Academies Press, 2000)
Ignition of upholstered furniture by small open flames from matches, cigarette lighters, and candles is one of the leading causes of residential-fire deaths in the United States. These fires accounted for about 16% of civilian fire deaths in 1996. On average, each year since 1990, about 90 deaths (primarily of children), 440 injuries, and property losses amounting to 50 million dollars have resulted from fires caused by the ignition of upholstered furniture by small open flames. Certain commercial seating products (such as aircraft and bus seats) are subject to flammability standards and sometimes incorporate FR-treated upholstery cover materials, but there is no federal-government requirement for residential upholstered furniture, and it is generally not treated with FR chemicals. It is estimated that less than 0.2% of all U.S. residential upholstery fabric is treated with flame-retardant (FR) chemicals. The Consumer Product Safety Act of 1972 created the U.S. Consumer Product Safety Commission (CPSC) as an independent federal regulatory agency whose mission is to protect the public from unreasonable risks of injury and death associated with consumer products. CPSC also administers the Flammable Fabrics Act, under which it regulates flammability hazards and the Federal Hazardous Substances Act (FHSA), which regulates hazardous substances including chemicals. In 1993, the National Association of State Fire Marshals petitioned CPSC to issue a performance-based flammability standard for upholstered furniture to reduce the risk of residential fires. The Commission granted that portion of the petition relating to small open flame ignition risks. In response to concerns regarding the safety of FR chemicals, Congress, in the fiscal year 1999 appropriations report for CPSC, requested that the National Research Council conduct an independent study of the health risks to consumers posed by exposure to FR chemicals that are likely to be used in residential upholstered furniture to meet a CPSC standard. The National Research Council assigned the project to the Committee on Toxicology (COT) of the Commission on Life Sciences' Board on Environmental Studies and Toxicology. COT convened the Subcommittee on Flame-Retardant Chemicals, which prepared this report. Subcommittee members were chosen for their recognized expertise in toxicology, pharmacology, epidemiology, chemistry, exposure assessment, risk assessment, and biostatistics. Toxicological Risks of Selected Flame-Retardant Chemicals is organized into 18 chapters and two appendices. Chapter 2 describes the risk assessment process used by the subcommittee in determining the risk associated with potential exposure to the various FR chemicals. Chapter 3 describes the method the subcommittee used to measure and estimate the intensity, frequency, extent, and duration of human exposure to FR chemicals. Chapters 4-19 provide the subcommittee's review and assessment of health risks posed by exposure to each of the 16 FR chemicals. Data gaps and research needs are provided at the end of these chapters.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2010 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2011)
This volume highlights the papers presented at the National Academy of Engineering's 2010 U.S. Frontiers of Engineering Symposium. Every year, the symposium brings together 100 outstanding young leaders in engineering to share their cutting-edge research and technical work. The 2010 symposium was held September 23 - 25, and hosted by IBM at the IBM Learning Center in Armonk, New York. Speakers were asked to prepare extended summaries of their presentations, which are reprinted here. The intent of this book is to convey the excitement of this unique meeting and to highlight cutting-edge developments in engineering research and technical work.

Assessment of Wingtip Modifications to Increase the Fuel Efficiency of Air Force Aircraft - National Research Council (The National Academies Press, 2007)
The high cost of aviation fuel has resulted in increased attention by Congress and the Air Force on improving military aircraft fuel efficiency. One action considered is modification of the aircraft2019s wingtip by installing, for example, winglets to reduce drag. While common on commercial aircraft, such modifications have been less so on military aircraft. In an attempt to encourage greater Air Force use in this area, Congress, in H. Rept. 109-452, directed the Air Force to provide a report examining the feasibility of modifying its aircraft with winglets. To assist in this effort, the Air Force asked the NRC to evaluate its aircraft inventory and identify those aircraft that may be good candidates for winglet modifications. This report2014which considers other wingtip modifications in addition to winglets2014presents a review of wingtip modifications; an examination of previous analyses and experience with such modifications; and an assessment of wingtip modifications for various Air Force aircraft and potential investment strategies.

Frontiers of Engineering: Reports on Leading-Edge Engineering from the 2005 Symposium - National Academy of Engineering; National Academy of Engineering (The National Academies Press, 2006)
This volume includes 16 papers from the National Academy of Engineering's 2005 U.S. Frontiers of Engineering (USFOE) Symposium held in September 2005. USFOE meetings bring together 100 outstanding engineers (ages 30 to 45) to exchange information about leading-edge technologies in a range of engineering fields. The 2005 symposium covered four topic areas: ID and verification technologies, engineering for developing communities, engineering complex systems, and energy resources for the future. A paper by dinner speaker Dr. Shirley Ann Jackson, president of Rensselaer Polytechnic Institute, is also included. The papers describe leading-edge research on face and human activity recognition, challenges in implementing appropriate technology projects in developing countries, complex networks, engineering bacteria for drug production, organic-based solar cells, and current status and future challenges in fuel cells, among other topics. Appendixes include information about contributors, the symposium program, and a list of meeting participants. This is the eleventh volume in the USFOE series.

Guidelines for Developing Spacecraft Maximum Allowable Concentrations for Space Station Contaminants - National Research Council (The National Academies Press, 1992)

NASA'S Role in Aeronautics: A Workshop - National Research Council (The National Academies Press, 1981)

Advanced Organic Composite Materials for Aircraft Structures: Future Program - National Research Council (The National Academies Press, 1987)

Outer Solar System: A Program for Exploration, Report of a Study - National Research Council (The National Academies Press, 1969)
Outer Solar System proposes a program for the exploration of the outer reaches of the solar system in the years 1974 to 1980. Of course, the technological requirements of the many-year missions and the vast distances represent new and difficult challenges in many technological areas such as communication, reliability, and miniaturization. This report presents a substantive account of the major scientific objectives of flight missions to the outer planets, and discusses the technical requirements in typical missions. This report complements the Space Science Board's 1968 study, Planetary Exploration: 1968-1975.

Report of the Committee on a Commercially Developed Space Facility - National Research Council (The National Academies Press, 1989)
The Committee on a Commercially Developed Space Facility assessed the scientific and commercial benefit to the nation of having a CDSF in place prior to Space Station operations. The committee examined planned and anticipated microgravity research and manufacturing requirements of the federal government and commercial users as well as the extent to which existing, planned, and proposed capabilities and infrastructure could support these requirements. The committee's findings concentrate on the desirability of having an additional space facility in service to the interim preceding Space Station Freedom.

Safe Passage: Astronaut Care for Exploration Missions - Institute of Medicine (The National Academies Press, 2001)
Safe Passage: Astronaut Care for Exploration Missions sets forth a vision for space medicine as it applies to deep space voyage. As space missions increase in duration from months to years and extend well beyond Earth's orbit, so will the attendant risks of working in these extreme and isolated environmental conditions. Hazards to astronaut health range from greater radiation exposure and loss of bone and muscle density to intensified psychological stress from living with others in a confined space. Going beyond the body of biomedical research, the report examines existing space medicine clinical and behavioral research and health care data and the policies attendant to them. It describes why not enough is known today about the dangers of prolonged travel to enable humans to venture into deep space in a safe and sane manner. The report makes a number of recommendations concerning NASA's structure for clinical and behavioral research, on the need for a comprehensive astronaut health care system and on an approach to communicating health and safety risks to astronauts, their families, and the public.

Methods for Developing Spacecraft Water Exposure Guidelines - National Research Council (The National Academies Press, 2000)
The National Aeronautics and Space Administration (NASA) maintains an active interest in the environmental conditions associated with living and working in spacecraft and identifying hazards that might adversely affect the health and well-being of crew members. Despite major engineering advances in controlling the spacecraft environment, some water and air contamination appears to be inevitable. Several hundred chemical species are likely to be found in the closed environment of the spacecraft, and as the frequency, complexity, and duration of human space flight increase, identifying and understanding significant health hazards will become more complicated and more critical for the success of the missions. NASA asked the National Research Council (NRC) Committee on Toxicology to develop guidelines, similar to those developed by the NRC in 1992 for airborne substances, for examining the likelihood of adverse effects from water contaminants on the health and performance of spacecraft crews. In this report, the Subcommittee on Spacecraft Water Exposure Guidelines (SWEGs) examines what is known about water contaminants in spacecraft, the adequacy of current risk assessment methods, and the toxicologic issues of greatest concern.

Spacecraft Water Exposure Guidelines for Selected Contaminants: Volume 3 - National Research Council (The National Academies Press, 2008)
NASA maintains an active interest in the environmental conditions associated with living and working in spacecraft and identifying hazards that might adversely affect the health and well-being of crew members. Despite major engineering advances in controlling the spacecraft environment, some water and air contamination is inevitable. Several hundred chemical species are likely to be found in the closed environment of the spacecraft, and as the frequency, complexity, and duration of human space flight increase, identifying and understanding significant health hazards will become more complicated and more critical for the success of the missions. To protect space crews from contaminants in potable and hygiene water, NASA requested that the National Research Council NRC provide guidance on how to develop water exposure guidelines and subsequently review NASA's development of the exposure guidelines for specific chemicals. This book presents spacecraft water exposure guidelines (SWEGs) for antimony, benzene, ethylene glycol, methanol, methyl ethyl ketone, and propylene glycol.

Readiness Issues Related to Research in the Biological and Physical Sciences on the International Space Station (The National Academies Press, 2001)

Recapturing a Future for Space Exploration: Life and Physical Sciences Research for a New Era - National Research Council (The National Academies Press, 2011)
More than four decades have passed since a human first set foot on the Moon. Great strides have been made in our understanding of what is required to support an enduring human presence in space, as evidenced by progressively more advanced orbiting human outposts, culminating in the current International Space Station (ISS). However, of the more than 500 humans who have so far ventured into space, most have gone only as far as near-Earth orbit, and none have traveled beyond the orbit of the Moon. Achieving humans' further progress into the solar system had proved far more difficult than imagined in the heady days of the Apollo missions, but the potential rewards remain substantial. During its more than 50-year history, NASA's success in human space exploration has depended on the agency's ability to effectively address a wide range of biomedical, engineering, physical science, and related obstacles2014an achievement made possible by NASA's strong and productive commitments to life and physical sciences research for human space exploration, and by its use of human space exploration infrastructures for scientific discovery. The Committee for the Decadal Survey of Biological and Physical Sciences acknowledges the many achievements of NASA, which are all the more remarkable given budgetary challenges and changing directions within the agency. In the past decade, however, a consequence of those challenges has been a life and physical sciences research program that was dramatically reduced in both scale and scope, with the result that the agency is poorly positioned to take full advantage of the scientific opportunities offered by the now fully equipped and staffed ISS laboratory, or to effectively pursue the scientific research needed to support the development of advanced human exploration capabilities. Although its review has left it deeply concerned about the current state of NASA's life and physical sciences research, the Committee for the Decadal Survey on Biological and Physical Sciences in Space is nevertheless convinced that a focused science and engineering program can achieve successes that will bring the space community, the U.S. public, and policymakers to an understanding that we are ready for the next significant phase of human space exploration. The goal of this report is to lay out steps and develop a forward-looking portfolio of research that will provide the basis for recapturing the excitement and value of human spaceflight2014thereby enabling the U.S. space program to deliver on new exploration initiatives that serve the nation, excite the public, and place the United States again at the forefront of space exploration for the global good.